2007
DOI: 10.1253/circj.71.1199
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Transplantation of Non-Expanded Peripheral Blood-Derived Mononuclear Cells Promotes Improvement of Cardiac Function in Patients With Acute Myocardial Infarction

Abstract: ifferentiation of mesodermal cells to angioblasts and subsequent endothelial differentiation was believed to exclusively occur in embryonic development, 1 but this dogma was overturned when human adult peripheral blood mononuclear cells (PBMNCs) were demonstrated to differentiate into the endothelial lineage. 2 These cells named "endothelial progenitor cells" (EPCs) expressed endothelial markers, and were incorporated into Circulation Journal Vol.71, August 2007 the sites of ischemia. 3,4 We have recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 41 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…Experimental and clinical studies of stem cell transplantation in the heart reveal that stem cells can differentiate into cardiac myocytes, endothelial cells, and secrete paracrine factors that reduce myocyte death, improve the microcirculation, attenuate adverse remodeling, and boost the regenerative capacity of the heart postinfarct. Unfortunately, the functional benefit seen following transplantation is modest at best, 1,7,9,13,16,[19][20][21]29 irrespective of the cell type and mode of delivery, because of very low levels of engraftment stemming from cell egress from the heart immediately following intra-myocardial cell delivery (low acute retention 30 ) and continued cell loss due to anoikis/apoptosis and necrosis (low engraftment 31,32 ). Low levels of cell engraftment results in small numbers of cells being available for cardiac differentiation and for secretion of paracrine factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and clinical studies of stem cell transplantation in the heart reveal that stem cells can differentiate into cardiac myocytes, endothelial cells, and secrete paracrine factors that reduce myocyte death, improve the microcirculation, attenuate adverse remodeling, and boost the regenerative capacity of the heart postinfarct. Unfortunately, the functional benefit seen following transplantation is modest at best, 1,7,9,13,16,[19][20][21]29 irrespective of the cell type and mode of delivery, because of very low levels of engraftment stemming from cell egress from the heart immediately following intra-myocardial cell delivery (low acute retention 30 ) and continued cell loss due to anoikis/apoptosis and necrosis (low engraftment 31,32 ). Low levels of cell engraftment results in small numbers of cells being available for cardiac differentiation and for secretion of paracrine factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to quantify engraftment in vivo and examine the influence of cell number on functional benefit and cardiac electrophysiology. PET and SPECT imaging have the potential to play a major role in pre-clinical and clinical studies of stem cell therapies because they provide information on myocardial viability, ejection fraction, infarct size, coronary flow reserve, and myocardial perfusion (which are important endpoints following stem cell transplantation) [1][2][3]6,7,9,[12][13][14]16,19,[21][22][23][24][27][28][29][35][36][37][38][39][40][41][42][43] in addition to permitting quantification of stem cell engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of bone marrow-derived cells has been shown to improve cardiac function in animal models of myocardial hibernation and myocardial infarction (MI) [1,2]. The cell therapy using bone marrow-derived stem cells was also found to be effective in patients with ischemic cardiomyopathy and acute myocardial infarction [3][4][5], although contradictory results have also been reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tastumi et al [40] reported that intracoronary infusion of non-expanded peripheral blood MNCs (5 × 10 9 cells) improved cardiac function in patients with myocardial infarction. In addition, hematopoietic progenitor cells (5.5 ± 3.9 × 10 6 ) purified from peripheral blood MNCs in TOPCARE-AMI trial improved cardiac function.…”
Section: Discussionmentioning
confidence: 99%